Key Factors for Private Sector Investment in Power Distribution - Pricewaterhousecoopers Securities (Washington, DC, 2014)
This paper was produced at the request of the Government of Uganda, as part of the ESMAP Power Restructuring Implementation Strategy in the country. On looking at the key factors that influence the private sector's evaluation of, and investment in power distribution firms worldwide, and, on the implications of the optimal role of multilateral institutions such as the Bank, this report provides the results of a study that Price Waterhouse Coopers Securities implemented on the subject, to assist the Bank in developing its policies regarding power distribution. Fundamental differences between distribution, and generation companies are highlighted: distribution companies must concern themselves with demand growth, retail markets, and customer concerns; while generation firms, tend to focus more on technical, and performance issues (owner separation from each segment of the industry, generally increase efficiency, and minimize undue market power). Surveys on overall country status, regulatory and legal framework, business practices and financial performances worldwide, show that while laws, and legislative systems are important factors (in their ability to repatriate funds - though arguably a part of the investment climate), financial performance stood by far, as the most important factor, i.e., the return on equity is critical, especially for publicly held investors, who must assess the impact of investments on stocks valuation. The role of multilateral institutions was seen as important in that it improves the investment climate through technical assistance, in that it promotes processes to achieve privatization, and restructuring country wise, and, in that it provides financing for power sector projects that require subsidies.